VALIDATION OF REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS DETERMINATION OF 6-, 8-, 10-GINGEROLS AND 6-SHOGAOL FROM GINGER EXTRACTS - ANTONY, BENNY; BENNY, MERINA; RESHMA, MARY (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: Development and validation of a High-Performance Liquid Chromatography (HPLC) method for the simultaneous estimation of 6-, 8-, 10-Gingerols and 6-Shogaol in ginger extract using authentic standards. Methods: The chromatographic separation was achieved by using a C18 column and a mobile phase composed of acetonitrile, ortho-phospohoric acid in water and methanol. The proposed method was validated in terms of the analytical parameters such as specificity, accuracy, precision, linearity, range, the limit of detection (LOD) and limit of quantification (LOQ) according to ICH guidelines. Results: Linear calibration curves were obtained over concentration ranges of 10-250 µg/ml for 6-, 8-, 10-gingerols and 6-shogaol with determination coefficients more than 0.99 for each analyte. Intra and inter-day precisions of the method were found to be below 2% for each analyte, with relative standard deviation (% RSD) values in the range of 0.47 to 1.55% for 6-gingerol, 0.44 to 1.51% for 8-gingerol, 0.24 to 1.90% for 10-gingerol and 0.25 to 1.67% for 6-shogaol. The percentage recovery of gingerols and shogaol was obtained with an average of 99.53%, 99.97%, 100.13% and 100.53% respectively, which was well within acceptance range. Conclusion: Simple, accurate, precise and rapid HPLC method was developed for the simultaneous analysis of 6-, 8-, 10-gingerols and 6-shogaol and validated in accordance with ICH guidelines. The developed method was found to be suitable for the standardization of herbal extracts and polyherbal formulations for the content of 6-, 8-, 10-gingerols and 6-shogaol.